Kinerja Aditif Improver dalam Produksi Rolling Oil Menggunakan Bahan Baku Minyak Sawit - M. Ainuri; T. T. Irawadi; A. Suryani; E. Gumbira-Sa’id; Z. A. Mas’ud; E. Hardono (agriTECH, 2008)
Rolling oil (RO) is a process lubricant that used in metal working industries, especially in cold rolling mill (CRM)process as roll coolants, roll oil and pickler oil. Rolling oil is the mixture of basic lubricant and additives. Basic lubricant of RO usually from mineral or synthetic oil which have problems on process performance as well as in en- vironment. Crude palm oil (CPO) is a potential commodity, but its’ utilities are still very limited. CPO is better than mineral or synthetic oil, especially on environmental conservation and process performance. Therefore, CPO is very potential to replace mineral oil as a base lubricant of RO. To determine the best base lubricant and additives based on characteristic analysis and performance uses two approaches, the statistical approach  used to know whether the treatment is effective or not and zero one method used to get the best decision from more alternatives and criteria. In general, CPO characteristics generally is similar with commercial RO characteristics. Yet, deviation of the acid value, peroxside value, iodine value, moisture and Fe content can be minimized by purification and mixture of olein fraction. Performance of improver additive, emulsifier (EM), viscocity index improver (VII) and extrime pressure (EP) produces three kinds of the best additive namely emulfluid A (Ed) as a emulsifier additive, AP. 5315 (Va) as a viscosity index improver and AP.2337 (Pb) as a extreme pressure. Interaction phenomena distinguish the more purify of CPO purification process the more interactive for additive, and interaction between additives distinguishes that additives of VII affect to emulsion performance and EP additives have negative effects on emulsion and viscosity performance. Selection of the best concentration of the best improver additives results; Ed 2.0 % (w/w) with alternative value of 35%, Va 2.0 % (w/w) with alternative value 42,9 % and Pb 2.0% with alternative value 46.25 %.ABSTRAKRolling oil (RO) adalah salah satu pelumas proses yang digunakan di industri logam, khususnya  pada proses coldrolling mill (CRM), berfungsi sebagai roll collants, roll oil dan pickler oil. Bahan utama RO adalah pelumas dasar dan aditif. Pelumas dasar RO pada umumnya berasal dari minyak bumi atau minyak sintetik yang memiliki permasala- han baik dalam kinerja proses maupun lingkungan. Minyak kelapa sawit (CPO) merupakan komoditas potensial, tetapi pemanfaatannya masih terbatas. CPO lebih baik dibanding minyak mineral dan sintetik khususnya terhadap konservasi lingkungan dan kinerja proses. Oleh kerena itu, CPO berpeluang menggantikan minyak mineral sebagai pelumas dasar RO. Pemilihan pelumas dasar dan aditif pada produksi RO didasarkan atas analisis karakteristik dan kinerja yang menggunakan dua pendekatan; statistik untuk mengetahui efektifitas perlakuan, dan metode  zero one untuk penentuan pilihan terbaik dari banyak alternatif dan kriteria. Secara umum, karakteristik CPO tidak jauh berbeda dengan karateristik RO komersial. Perbedaan pada bilangan asam, peroksida, dan iod, serta kadar air dan kadar Fe dapat diperkecil melalui proses purifikasi dan pencampuran fraksi olein. Kinerja aditif improver, emulsifier (EM), viscocity index improver (VII) dan extreme pressure (EP) diperoleh tiga macam aditif terbaik, yaitu emulfluid A (Ed) sebagai aditif emulsifier, AP. 5315 (Va) aditif viscosity index improver dan AP.2337 (Pb) aditif extreme pressure. Fenomena interaksi CPO dangan aditif menunjukkan semakin murni CPO semakin kuat dan interaksi antara aditif dengan aditif menunjukkan bahwa aditif VII berpengaruh positif terhadap kinerja emulsi dan aditif EP negatif terh- adap kinerja emulsi dan viskositas.  Sedang konsentrasi aditif improver terbaik  adalah Ed 2.0 % (w/w) dengan nilai alternatif  35 %, Va  2.0 % (w/w) dengan nilai alternatif  42,9 % dan Pb  2.0%  dengan nilai alternatif  46.25 %.